Properties of Bacterial Cellulose/Polyvinyl Composite Membrane for Polymer Electrolyte Li ion Battery - qolby sabrina; Hilwa Kamilah; Christin Rina Ratri; Titik Lestariningsih; Sitti Ahmiatri Saptari (Chemistry Department, The University of Brawijaya, 2023)
High ionic conductivity and more porous have extraordinary significance to solid polymer electrolyte in Li ion battery application. In this study, bacterial cellulose (BC) based polymer was modified by polyvinyl pyrrolidone (PVP) and polyvinyl acetate (PVA) to get composite solid polymer electrolyte. Blending the polymer host is one more approach to work on the morphology pore and electrochemical properties of polymer electrolytes. The slurry of BC is rich in fibers that contribute to forming the pore template of the solid electrolyte membrane. Polyvinyl work to make more pore and increases the polymer segmental ion lithium mobility. Pore morphology of BC PVA composite membrane homogeneously distributed by SEM observations. The presence of many pores makes the tensile strength of the BC PVA membrane lower, for use in solid electrolytes it does not affect battery performance. The presence of pores that contribute a lot to the absorption of electrolytes. Enhancement of the conductivity upon addition of salt is correlated to the enhancement of more pore of polymer electrolyte. The conductivity of BC PVA composite 8.45 x 10-7 Scm-1 higher than PVP at room temperature. In the future, PVA can be relied on to be a mixed material for solid electrolyte membranes based on cellulose.